2011
DOI: 10.1017/s204017441100078x
|View full text |Cite
|
Sign up to set email alerts
|

Diverse ability of maternal immune stimulation to reduce birth defects in mice exposed to teratogens: a review

Abstract: Stimulating the maternal immune system before or during pregnancy can dramatically improve morphologic outcome in mice that have been exposed to teratogens. For example, maternal immune stimulation in mice reduced craniofacial and palate defects, heart defects, digit and limb defects, tail malformations and neural tube defects caused by diverse teratogens that included chemical agents, hyperthermia, X-rays and diabetes mellitus. Several different procedures of immune stimulation were effective and included foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…It has been experimentally demonstrated that maternal immune stimulation can reduce the incidence of diabetic craniofacial embryopathy 60,61 . Furthermore, birth defects in mice exposed to teratogens can be reduced by select immunostimulatory treatments, such as immune modulation of cytokines before or during pregnancy 62,63 . Studies have shown that several acute phase reactive protein and complement components, such as C1q and C3a, increase in maternal blood circulation during normal pregnancy 64 …”
Section: Discussionmentioning
confidence: 99%
“…It has been experimentally demonstrated that maternal immune stimulation can reduce the incidence of diabetic craniofacial embryopathy 60,61 . Furthermore, birth defects in mice exposed to teratogens can be reduced by select immunostimulatory treatments, such as immune modulation of cytokines before or during pregnancy 62,63 . Studies have shown that several acute phase reactive protein and complement components, such as C1q and C3a, increase in maternal blood circulation during normal pregnancy 64 …”
Section: Discussionmentioning
confidence: 99%
“…VPA‐induced open NT is associated with increased apoptosis localized to the midline of the NT in GD9 mouse embryos (Hrubec et al, ; Tung & Winn, ). Active pStat3 is required for the induction of the antiapoptotic protein (Fukada, Hibi, & Yamanaka, ) and previously VPA has been shown to downregulate Bcl2 protein expression by approximately three‐fold in both VPA‐treated open NT and closed NT embryos in comparison to control embryos (Dawson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonspecific stimulation of the maternal immune system in mice reduces a wide variety of teratogen‐induced fetal malformations (Hrubec et al., ). Many different immunologically active agents and stimulation regimes have proved effective in reducing fetal malformations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many maternal cytokines can cross the placenta and reach the embryos. It is possible that increased levels of maternal cytokines resulting from immune stimulation prevent teratogenic effects on normal morphogenic processes such as cell proliferation and apoptosis in the embryo (Hrubec et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation